Potassium channels in cancer: from hallmarks to therapeutic targeting - Yi-ling Zhang; Rong-jia Shi; Xin-hua Liang (Journal of Physiology and Biochemistry, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Continuous coagulant and alkali dosing enhanced organic separation from hypersaline wastewater in synchronous ozonation coagulation process - Yuhan Yang; Mengwen Liu; Rong Liu; Yiqiao Shi; Yadong Wang; Yukai Zong; Zimin Lu; Xu Lu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Mineralogical tracers for magmatic and hydrothermal controls on Nb-Ta-Li mineralization: a case study from the Hailuoling granite system, Southern China - Qifei Shi; Bin Wu; Xin Gui; Qian Ren; Guanglai Li; Rong Yin; Qingfei Wang (Mineralium Deposita, 2026)

A deep learning-based prognostic approach for predicting PWR degradation and remaining useful life using GNN-PTC-LSTM - Shadman Ahmad Khattak; Liu Yong-Kuo; Liu Yu-Kun; Gao Jia-Rong; Shi Zhou-Xin; Liu Ji (Annals of Nuclear Energy, 2026)

Synergistic antifouling and organic removal using Fe/N co-doped biochar-modified ceramic membranes via in situ peroxymonosulfate activation - Rong Liu; Ye Zhu; Peng Ren; Jinge Fan; Yadong Wang; Mengwen Liu; Yabo Shang; Lu Xu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Chemical Engineering Journal, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Global patterns and soil controls governing terrestrial nitrogen cycling in response to experimental warming: A meta-analysis - Sen-Mao Zhang; Wan-Jia Hu; Xin-Rong Shi; Robert L. Kallenbach; Zhi-You Yuan (Soil Biology and Biochemistry, 2026)

The role of heterogeneity in groundwater chemistry and mixing within the critical zone of a volcanic rock hillslope - Tao Yang; Jiu Jimmy Jiao; Rong Mao; Xin Luo; Jeffrey Wong; Jinchao Zuo; Wenli Hu; Jiawei Liang; Yanqiong Huang; Xiaoyan Shi (Journal of Hydrology, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Identification of a novel selenium peptide from Oryzain α hydrolysate: Selenium-specific database establishment, sequence confirmation, and molecular interaction analysis - Xin Wang; Bailiang Xue; Rong Zhang; Lin Shi; Wei Jia (Food Bioscience, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Fluvial response to differential activity of the Litang fault system: Implications for fault kinematics and geodynamics in the southeastern Tibetan Plateau - Jinhan Wang; Xuhua Shi; Rong Yang; Hanlin Chen; Huili Yang; Yuanhai Shu; Zhuona Bai; Chenchao Xu; Xin Liu (Geomorphology, 2025)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

Multi-scale piezoresistive foam composed of graphene skeleton and vertical WS2 nanosheets designed for wearable detection/protection applications - Tengyue Song; Minxuan Xu; Yueqin Shi; Xin Li; Hang Wang; Zhe Kong; Suyu Sheng; Qi Zhang; Rong Xiang (Chemical Engineering Journal, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Bioturbation and the effects on benthic flux of nitrogen in a large eutrophic lake: Insights from 224Ra/228Th disequilibrium and inverse geochemical modelling - Xiaoyan Shi; Guodong Chen; Rong Mao; Xin Luo; Jiu Jimmy Jiao; Meiqing Lu; Tianwei Wang; Wenli Hu; Xingxing Kuang (Geochimica et Cosmochimica Acta, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Amelioration impact of gut-brain communication on obesity control by regulating gut microbiota composition through the ingestion of animal-plant-derived peptides and dietary fiber: can food reward effect as a hidden regulator? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Study on the Rules of Ground Settlement and Pipeline Deformation Considering the Combined Effects of Pipeline Damage Leakage and Shield Tunneling Construction - Xin Shi; Liang Zheng; Chuanxin Rong; Hua Cheng; Haibing Cai; Taihong Li (Transportation Geotechnics, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Exploring novel ANGICon-EIPs through ameliorated peptidomics techniques: Can deep learning strategies as a core breakthrough in peptide structure and function prediction? - Wei Jia; Jian Peng; Yan Zhang; Jiying Zhu; Xin Qiang; Rong Zhang; Lin Shi (Food Research International, 2023)

Biology and morphology of the larvae of Uropyia meticulodina (Lepidoptera: Notodontidae), with discussion on their feeding and defensive strategies - Jia-Xin Liu; Di Zhao; Hui-Rong Hu; Yi-Yi Liu; Shi-Ci Zhao; Lu Jiang (Zoomorphology, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Protein tyrosine phosphatase 1B expression contributes to the development of breast cancer - Shi-chong Liao; Jin-xin Li; Li Yu; Sheng-rong Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Interlocking Intramedullary Nails in Fracture Treatment - Xiao Ouyang; Jing Rong Wang; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Jian Wang (Cell Biochemistry and Biophysics, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Silicon-mediated amelioration of zinc toxicity in rice (Oryza sativa L.) seedlings - Hai-Hong Gu; Shu-Shun Zhan; Shi-Zhong Wang; Ye-Tao Tang; Rufus L. Chaney; Xiao-Hang Fang; Xin-De Cai; Rong-Liang Qiu (Plant and Soil, 2012)

Ocular Pharmacokinetic Study Using T1 Mapping and Gd-Chelate- Labeled Polymers - Xianfeng Shi; Xin Liu; Xueming Wu; Zheng-Rong Lu; S. Kevin Li; Eun-Kee Jeong (Pharmaceutical Research, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Genetic Diversity and Geographical Differentiation of Desmodium triflorum (L.) DC. in South China Revealed by AFLP Markers - Mao-feng Yue; Ren-chao Zhou; Ye-lin Huang; Guo-rong Xin; Su-hua Shi; Li Feng (Journal of Plant Biology, 2010)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)